Student’s Motivation of Counseling in Entrepreneurs - Yulianto (Program Studi S3 Ilmu Manajemen, 2020)
The aim of the study was explored student’s motivation for Guidance and Counseling major at STKIP Muhammadiayah Pringsewu in entrepreneurship. The results of research can be concluded that the study involved three subjects, namely STKIP Muhammadiyah Pringsewu students who were entrepreneurs. The three subjects came from the Department of Counseling Guidance. The three subjects are from different semesters. The first subject was entrepreneurship in selling Muslim clothing and equipment, the second subject was entrepreneurship in the field of selling food and beverages, and the third subject was entrepreneurship in the field of typing services. The three subjects in this study had different entrepreneurial motivations, DMS had a motive for self-development, ASP had an independence motive, and the AL had income motives. Students who are entrepreneurs is not only because of their income, but the subject prioritizes the interests of their studies compared to entrepreneurs, this is because the subject does not pursue the income target of the entrepreneur, while the subject makes the entrepreneur as source of income that meets the economic needs of his life, when there are things that must be solved simultaneously between study and entrepreneurship, subjects tend to choose entrepreneurship, because entrepreneurship can provide income that can meet their daily needs and meet their security needs.